Predicting odor from molecular structure: a multi-label classification approach - Saini, Kushagra; Ramanathan, Venkatnarayan (Nature Research, 2022)
Decoding the factors behind odor perception has long been a challenge in the field of human neuroscience, olfactory research, perfumery, psychology, biology and chemistry. The new wave of data-driven and machine learning approaches to predicting molecular properties are a growing area of research interest and provide for significant improvement over conventional statistical methods. We look at these approaches in the context of predicting molecular odor, specifically focusing on multi-label classification strategies employed for the same. Namely binary relevance, classifier chains, and random forests adapted to deal with such a task. This challenge, termed quantitative structure–odor relationship, remains an unsolved task in the field of sensory perception in machine learning, and we hope to emulate the results achieved in the field of vision and auditory perception in olfaction over time.
This paper is submitted by the author of IIT (BHU), Varanasi
Keywords: Humans; Machine Learning; Molecular Structure; Odorants; Olfactory Perception; Smell; fragrance; chemical structure; human; machine learning; odor; smelling